การเหนี่ยวนำโปรเฟจที่แทรกอยู่ใน Lactobacillus paracasei ที่แยกได้จากนมเปรี้ยว - สุนทรธรรมาสน์, สิรินธร; Doi, Katsumi; สุวรรณาศรัย, ณัฎฐิกา; รังษิรุจิ, อัจฉริยา; พริ้งศุลกะ, อรอนงค์ (Science Essence Journal, 2017)
บทคัดย่อ Lactobacillus (Lb.) paracasei ถูกนำมาใช้เป็นหัวเชื้อในการผลิตผลิตภัณฑ์นมหมักหลากหลายชนิด อย่างไรก็ตาม ปัญหาหลักที่เกิดขึ้นในการผลิตนมหมักคือ การปนเปื้อนด้วยเฟจซึ่งส่งผลให้การหมักในโรงงานผลิตนมหมักเกิดช้าลงหรือไม่สมบูรณ์ การศึกษาของกลุ่มผู้วิจัยก่อนหน้านี้ได้แยกเชื้อ Lb. paracasei LPC จากผลิตภัณฑ์นมเปรี้ยว ซึ่งค้นพบว่าในหัวเชื้อนี้มีโปรเฟจแทรกอยู่และจะสามารถหลุดออกมาได้เป็นครั้งคราวโดยการเหนี่ยวนำที่เกิดขึ้นได้เองตามธรรมชาติ แต่การเกิดการเหนี่ยวนำลักษณะนี้มักไม่ได้เหนี่ยวนำได้ทุกครั้งหรือไม่สามารถคาดการณ์ได้ ดังนั้นงานวิจัยนี้จึงมีวัตถุประสงค์ในการเหนี่ยวนำโปรเฟจที่แทรกอยู่ใน Lb. paracasei LPC รวมทั้งทดสอบในสายพันธุ์กลายที่ดื้อต่อการติดเชื้อด้วยเฟจอีก 10 ไอโซเลตด้วยรังสียูวีและสารไมโตมัยซินซีรวมถึงสภาวะต่างๆ ในระหว่างการหมักนม ผลการทดลองพบว่า การเหนี่ยวนำโปรเฟจของเชื้อจะเกิดขึ้นโดยอาศัยไมโตมัยซินซีเท่านั้น นอกจากนี้ไมโตมัยซินซียังสามารถเหนี่ยวนำโปรเฟจที่แทรกอยู่ในสายพันธุ์กลายที่ดื้อต่อการติดเชื้อด้วยเฟจอีก 3 สายพันธุ์ด้วย จากการศึกษานี้จึงเห็นได้ว่า ระบบการกดการเหนี่ยวนำให้โปรเฟจหลุดในเชื้อกลุ่มนี้เพื่อให้โปรเฟจคงอยู่ในสภาวะพักเป็นระบบที่ซับซ้อน Prophage Induction in Lactobacillus paracasei Isolated from Fermented Milk ABSTRACT Lactobacillus paracasei has been used as a starter for manufacturing of various fermented dairy products. However, one of the main problems of dairy production is the contamination of phages which leads to slow or incomplete fermentation in the dairy industry. In our previous study, Lb. paracasei LPC which was isolated from one of the fermented milk products was found to harbor a prophage. This prophage may be released by spontaneous induction of Lb. paracasei LPC but this phenomenon was unpredictable. Therefore, the present study aimed to induce the prophages from the lysogenized Lb. paracasei LPC and 10 phage resistant mutant strains by using standard inducing agent (ultraviolet radiation and mitomycin C). Certain culture conditions in the fermented milk production were also investigated to determine the possibility of these phages being induced. The results showed that the strong induction of the prophages in the lysogenized Lb. paracasei LPC was obtained only when the mitomycin C was employed. This type of inducible phages was also generated from other three resistant strains. These findings revealed that the repression system that maintains the prophages in the dormant state in lactobacilli strains is sophisticated.